2009
DOI: 10.1073/pnas.0812414106
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical principles that regulate the competition between functional and dysfunctional association of proteins

Abstract: To maintain protein homeostasis, a variety of quality control mechanisms, such as the unfolded protein response and the heat shock response, enable proteins to fold and to assemble into functional complexes while avoiding the formation of aberrant and potentially harmful aggregates. We show here that a complementary contribution to the regulation of the interactions between proteins is provided by the physicochemical properties of their amino acid sequences. The results of a systematic analysis of the protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 35 publications
9
153
0
7
Order By: Relevance
“…The effect of these regions is similar to the role of "gatekeeping" residues preventing nonspecific aggregation (41,51). Disabling regions prevent any aggregation or association with other partners and might be specific in the sense of preventing the participation in nonspecific functional pathways assisting the functional separation of paralogs.…”
Section: Enabling and Disabling Regions Are Important For Developing Newmentioning
confidence: 70%
See 1 more Smart Citation
“…The effect of these regions is similar to the role of "gatekeeping" residues preventing nonspecific aggregation (41,51). Disabling regions prevent any aggregation or association with other partners and might be specific in the sense of preventing the participation in nonspecific functional pathways assisting the functional separation of paralogs.…”
Section: Enabling and Disabling Regions Are Important For Developing Newmentioning
confidence: 70%
“…Unlike amino acid composition analysis the aggregation propensity calculations take into account the residue context, the presence of specific patterns of alternating hydrophobic and hydrophilic residues, and residue charges. A recent study by Pechmann et al (41) reported that interfaces of protein complexes are more prone to aggregate than surface. Consistent with this study we found similar trends for homooligomers (Wilcoxon signed-rank test p-value < 10e−10, Fig.…”
Section: Mechanism Of Dimerization Through Insertions/deletions Of Prmentioning
confidence: 99%
“…Second, disease-causing mutations can lead to perturbations in the PPI networks in affected tissues, thereby influencing pathogenesis. Changes in functional protein interactions are frequently linked to changed protein levels in cells; both phenomena have been shown to favor spontaneous protein misfolding and are indicators that a protein might influence HTT aggregation and HD pathogenesis (Pechmann et al 2009;Vavouri et al 2009). Therefore, we reasoned that HTT interaction partners displaying abnormal changes in abundance in regions of the brain that are particularly vulnerable to HD may be disease-relevant modifiers that influence mutant HTT misfolding and aggregation.…”
mentioning
confidence: 99%
“…Even among the binding interface residues that contribute to the binding affinity, the degree of amino acid sensitivity between similar amino acids is unclear. It has been suggested that a small subset of electrostatic residues may drive specificity in a sea of hydrophobic interactions driving affinity (Pechmann et al, 2009). Changes in untranslated regions can also affect mRNA stability, but have not been factored into the view described above.…”
Section: Mutational Opportunities After Duplicate Gene Birthmentioning
confidence: 99%